2021
DOI: 10.1007/s00122-021-03875-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica)

Abstract: Panicle architecture and grain weight, both of which are in uenced by genetic and environmental factors, have signi cant effects on grain yield potential. Here, we used a recombinant inbred line population (RIL) of 333 lines, which were grown in 13 trials with varying environmental conditions, to identify quantitative trait loci (QTL) that control differences in 9 agronomic traits related to panicle architecture and grain yield.We nd that panicle weight, grain weight per panicle, panicle length, panicle diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Furthermore, QTL for some negatively correlated traits, such as qSD9.1 and qGNS9.1, belonged to the same cluster 9.2. These results indicate that there was a presence of genetic linkage or pleiotropy effects among traits with significant correlation (Fang et al 2016 ; Zhi et al 2021 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, QTL for some negatively correlated traits, such as qSD9.1 and qGNS9.1, belonged to the same cluster 9.2. These results indicate that there was a presence of genetic linkage or pleiotropy effects among traits with significant correlation (Fang et al 2016 ; Zhi et al 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…The QTL cluster was defined as a chromosome region harboring multiple QTL for various traits within ~ 20 cM (Tan et al 2018 ). And phenotypically correlated traits are often mapped to similar genomic regions (Zhi et al 2021 ). Of 221 QTL for seventeen traits, 130 with overlapping intervals formed 22 QTL clusters (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies were based on a small number of polymorphic loci, and fewer QTL were identified. A recent QTL mapping study based on 12 environments identified 159 QTLs associated with panicle-related traits, which improved our understanding of the genetic basis for panicle and yield formation in foxtail millet [ 17 ]. However, QTL results based on bi-parental populations are heavily dependent on the genetic background of the population and environment, which greatly limits the wide adaptability and stability of these QTLs in foxtail millet breeding programs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%